Sekulární trend v tělesné výšce a hmotnosti dospělé populace v České republice - Kopecký, Miroslav; Kikalová, Kateřina; Charamza, Jiří (Casopis lekaru ceskych, 2016)
Secular changes in anthropometric parameters reflect the effect of socio-economic conditions in interaction with other factors on individuals in the course of 100-200 years. The main aim of the research was to determine the average body height and weight for the current adult population of men 19 to 94 years old and women 19 to 86 years old in the Czech Republic, and to compare the average values ​​of body height and weight of the monitored group with the reference values ​​for the adult population observed in our country from 1895 to 2001.Body height and weight were measured with standard anthropometry in 973 men aged 19-94 years and 2,606 women aged 19-86 years. The research was carried out from 2013 to 2015. Statistical tests: t-test, one-way analysis of variance (ANOVA). The average body weight and height of the current adult male is 178.58 cm and 80.86 kg, and of adult female 165.99 cm and 65.67 kg. When compared to men, women show significantly lower average height by 12.59 cm and lower weight by 15.19 kg. The results show that men today are about 10.61 cm higher and weigh 9.01 kilograms more than men in 1895. Todays women are about 9.43 centimeters taller, but weigh 0,58 kg less than women of the same age in 1895.Comparison of results from 1895 to 2015 shows that at present there is likely stagnation or decline in the positive secular trend in body height among men and women. The weight of men is increasing while there is stagnation in the body weight of women.
Keywords: senioři; senioři nad 80 let; body height; adult population; Sex Distribution; secular trend anthropological surveys.; Age Distribution; Česká republika; Middle Aged; mužské pohlaví; Body Height; Adult; mladý dospělý; Czech Republic; Body Weight; Aged, 80 and over; Young Adult; ženské pohlaví; Anthropometry; Humans; věkové rozložení; tělesná hmotnost; lidé středního věku; body weight; antropometrie; dospělí; rozložení podle pohlaví; Female; Aged; tělesná výška; lidé; Male